Proyecto de investigación estudio de las Instituciones para el financiamiento de las Mipymes con potencial exportador de los sectores de turismo y turismo en salud del departamento del Quindío (2013)
This project aims to identify and classify the institutions of local and national character that conduct foreign trade financing for Mipyme in Colombia, the financing terms and the use of credit lines in the tourism and health sectors of Quindío. For this purpose the financial hierarchy theory, the Colombia´s Financial Superintendence and Trade Off Theory was considered; and it was necessary to research all financial and nonfinancial entities that offer credit´s lines to Mipyme in Colombia. Additionally, it was necessary to do a survey of 102 employers in the tourism and health sectors to determine the use they give to credit lines. From the above, it was established that there is a wide range from financial and nonfinancial institutions to strengthen Mipyme; they offer different credit lines that become growth and strengthening tools that adapt to business needs. It is recommended that employers should be formalized (for those who have not already done), evaluate different entities when applying for loans, develop management skills to negotiate interest rates according to the amounts and time frame, considering rediscount lines and access to training in the use of instruments that gives the financial sector.